A Case of Recalcitrant Epidermolysis Bullosa Acquisita Responsive to Rituximab Therapy. Issue 2 (29th October 2012) - McKinley, Sophia K.; Huang, Jennifer T.; Tan, Jennifer; Kroshinsky, Daniela; Gellis, Stephen
Abstract Epidermolysis bullosa acquisita (EBA) is an autoimmune blistering disorder that occurs infrequently in children. Although typically associated with a good prognosis in children, there are rare cases that are refractory to treatment with conventional immunosuppressive therapy. Rituximab, an anti‐CD20 monoclonal antibody, has been reported to be effective in the adult form of EBA. We report a case of a child with severe and recalcitrant EBA exhibiting a sustained response to treatment with rituximab.